2020
DOI: 10.1016/j.ebiom.2020.102728
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genomic insights into circulating tumor DNA-based alterations across the spectrum of metastatic hormone-sensitive and castrate-resistant prostate cancer

Abstract: Background: Metastatic prostate cancer is a clonally heterogeneous disease state characterized by progressive somatic perturbations. The aim of this study was to identify cell free DNA-(cfDNA-) based alterations and their associations with outcomes in progressive metastatic prostate cancer. Methods: In this longitudinal prospective cohort study plasma cfDNA/circulating tumor DNA (ctDNA) was analyzed before, during, and after androgen deprivation therapy (ADT) in 4 independent patient groups ranging from untrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 38 publications
4
76
0
Order By: Relevance
“…AR amplification has been previously reported in several independent studies to prognosticate survival in mCRPC state, and our group recently also reported AR-En amplification was associated with primary resistance to abiraterone acetate treatments [ 4 , 25 , 30 ]. We now report a quantitative, sensitive four CN altered targets-based multiplex dPCR assay to detect CN changes in AR -En, AR- E1, AR -E8, and OPHN1 genes using cfDNA from plasma of mCRPC patients.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…AR amplification has been previously reported in several independent studies to prognosticate survival in mCRPC state, and our group recently also reported AR-En amplification was associated with primary resistance to abiraterone acetate treatments [ 4 , 25 , 30 ]. We now report a quantitative, sensitive four CN altered targets-based multiplex dPCR assay to detect CN changes in AR -En, AR- E1, AR -E8, and OPHN1 genes using cfDNA from plasma of mCRPC patients.…”
Section: Discussionmentioning
confidence: 85%
“…cfDNA was extracted from plasma and pre-amplified by using a ThruPlex DNA-Seq Kit (Rubicon Genomics, Ann Arbor, MI, USA) as previously described [ 30 ]. The target regions were selected based on our previous sequencing data showing amplification at genomic AR loci, including AR -En, AR , and OPHN1 in mCRPC patients [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…A prospective study evaluating ctDNA fluctuations before, during and after ADT initiation showed that patients with mHSPC and cfDNA levels above the median (9.6 ng/mL) had shorter time to progression to CRPC compared to those who did not (HR 2.29, 95% CI 1.13–4.65; log-rank p =0.02). 80 When stratified by CHAARTED-defined volume status, a high-volume burden had higher levels of cfDNA yield compared to low-volume disease (median 5.82 ng/mL versus 3.96 ng/mL; p =0.04). Not surprisingly, it was found that a combination of CHAARTED-defined high-volume disease burden and increased ctDNA had the highest rate of ADT failure and worse OS (log-rank p =0.03 for both).…”
Section: Predictive Markersmentioning
confidence: 92%
“…Quite recently, Kohli et al reported the results of a longitudinal study involving plasma cfDNA/ctDNA evaluation performed prior to, during, and after androgen deprivation therapy, in various groups of prostate cancer patients ranging from untreated metastatic hormone-sensitive patients to the metastatic castration-resistant tumor bearing ones. [156]. The study involved the use of next-generation sequencing on ctDNA, and the results demonstrated that: the cfDNA levels in progressive hormone-sensitive patients were different from those in the hormone-resistant patients; in hormone-sensitive patients, higher ctDNA fraction was predictive of a shorter time for progression to androgen independency; cfDNA and ctDNA values, together with the volume of metastatic disease were highly predictive of survival; and ctDNA mutations were more frequent among the androgen-independent patients compared to the androgen-sensitive ones, with the TP53 mutations, RB1 loss, and AR gene amplifications correlating with poorer survival [156].…”
Section: Prostate Cancermentioning
confidence: 99%
“…[156]. The study involved the use of next-generation sequencing on ctDNA, and the results demonstrated that: the cfDNA levels in progressive hormone-sensitive patients were different from those in the hormone-resistant patients; in hormone-sensitive patients, higher ctDNA fraction was predictive of a shorter time for progression to androgen independency; cfDNA and ctDNA values, together with the volume of metastatic disease were highly predictive of survival; and ctDNA mutations were more frequent among the androgen-independent patients compared to the androgen-sensitive ones, with the TP53 mutations, RB1 loss, and AR gene amplifications correlating with poorer survival [156]. These findings further support the consistent clinical utility of ctDNA evaluation in refining the prognosis in metastatic prostate cancer patients.…”
Section: Prostate Cancermentioning
confidence: 99%